BSCI-14. tGLI1 is an actionable therapeutic target in breast cancer brain metastases. (9th August 2021) - Doheny, Daniel; Manore, Sara; Wong, Grace; Zhu, Dongqin; Sirkisoon, Sherona; Rimkus, Tadas; Anguelov, Marlyn; Aguayo, Noah; Regua, Angelina; Cox, Anderson O'Brian; Furdui, Cristina; Thomas, Alexandra; et al.
Abstract: Breast cancer is the second leading cause of brain metastases in women; patients with breast cancer brain metastasis (BCBM) survive a median of 14.1 months following diagnosis. Cancer stem cells are thought to be one of the driving forces behind distant metastasis, treatment resistance, and late-stage recurrence. Despite advances made in understanding breast cancer stem cells (BCSC), it remains challenging to effectively target BCSC underscoring the need to identify and inhibit novel mediators of BCSC for treating BCBM patients. The hedgehog-smoothened pathway is an important mediator of breast cancer stem cells (BCSC); however, FDA-approved therapies targeting smoothened have demonstrated limited clinical efficacy in breast cancer. Truncated glioma-associated oncogene homolog 1 (tGLI1) was discovered in our laboratory as an alternative GLI1 splice variant that functions as a tumor-specific gain-of-function transcription factor and terminal effector of the hedgehog pathway. Our laboratory recently reported that tGLI1 promotes preferential metastasis to the brain in breast cancer by activating BCSC and astrocytes in the tumor microenvironment (Oncogene 39:64–78, 2020). tGLI1 knockdown abrogated BCBM, providing the rationale to therapeutically target tGLI1. This study aimed to determine if tGLI1 can be therapeutically targeted. Cell-based chemical screens followed by validations demonstrated that ketoconazole, an FDA-approved azole antifungal, and novel derivatives specifically inhibit tGLI1 leading to suppression of BCSC in vitro and BCBM in vivo . Mechanistic studies suggest that KCZ-dependent cell kill is, in part, mediated through downregulation of tGLI1 target genes OCT4, Nanog, and VEGFA . Based on these data, we opened a window-of-opportunity study in patients with BCBM to determine if ketoconazole penetrates the blood-brain barrier (BBB) and alters tGLI1 signaling in humans (NCT03796273). Preliminary sample analysis demonstrates ketoconazole crosses the blood-tumor barrier and that tGLI1 expression correlates with tGLI1 signaling in resected samples. Collectively, these data establish tGLI1 as an actionable target for BCBM.